Analogue-digital dialectics in architectural design. Towards renewed hypotheses of method - Giuseppe Canestrino (Agathón)
The dichotomy between analogue and digital influences the methods of design, production, construction, as well as the formal horizons of architecture. This dichotomy is apparently only related to the contemporary situation in which architecture is thought, built, and managed in increasingly computerised ways, and is consequently distanced from its more concrete aspects. However, a deep understanding of the meanings of analogue and digital reveals a dialectical relationship that can be looked to in order to renew aspects of the method of architectural design.